Studying the influence of vibration on the process of obtaining semi-finished products for distillery production - N. Yu. Kachaeva; N. N. Maleev; Kh. E. Kachaev (Новые технологии, 2024)
Liquor products are represented by a wide range of drinks. Despite this diversity, they are all united by the use of semi-finished products (alcoholic juices, pestilences and infusions) during blending. Extraction of components of plant raw materials is one of the key processes for obtaining semi-finished alcoholic beverages. The quality indicators of the finished liquor product directly depend on their composition and quality. The purpose of the research is to study the vibration effect as a physical method of intensifying the process of extracting flavoring and aromatic compounds of fruit and berry raw materials when obtaining semi-finished products for distillery production (infusions and juices). To study the effect of vibration exposure on the content of substances responsible for taste, such technical factors as frequency (f), amplitude (A) and duration (τ) of exposure have been taken into account. The mass concentration of phenolic and coloring substances has been taken as controlled indicators. The processing was carried out on the installation developed at the Department of Winemaking and Fermentation Technology named after Professor A.A. Merzhanyan of FSBEI HE «KubSTU». The research was conducted on semi-finished products obtained from raspberries and cherries in the process of obtaining alcoholized components of a blend of liqueurs. In this case, the ratio of components was equal to 1:1. A comparison of the indicators was carried out with a sample obtained by stationary infusion. The positive influence of vibration during the extraction process with aqueous-alcohol solutions on the quality indicators of semi-finished products was established. Optimal processing parameters were also determined to reduce the duration of the process. The data obtained allow us to judge the feasibility of using vibration in the alcoholic beverage industry as a technique that accelerates infusion and improves the quality of semi-finished products.